2021
DOI: 10.48550/arxiv.2102.03006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learned Phase Transitions in a System of Anisotropic Particles on a Square Lattice

Abstract: The area of Machine learning (ML) has seen exceptional growth in recent years. Successful implementation of ML methods in various branches of physics has led to new insights. These methods have been shown to classify phases in condensed matter systems. Here we study the classification problem of phases in a system of hard rigid rods on a square lattice around a continuous and a discontinuous phase transition using supervised learning (with prior knowledge about the transition points). On comparing a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The transition has been rigorously established to exist in two dimensions [11], and is also seen in the exactly soluble case of k-mers on tree-like lattices [12]. It has also been shown that machine learning can be used to detect this phase transition [13].…”
Section: Introductionmentioning
confidence: 95%
“…The transition has been rigorously established to exist in two dimensions [11], and is also seen in the exactly soluble case of k-mers on tree-like lattices [12]. It has also been shown that machine learning can be used to detect this phase transition [13].…”
Section: Introductionmentioning
confidence: 95%
“…Often times the data are flattened somewhere in the network, as e.g. in [21][22][23][24][25][26], and sometimes a convolutional or pooling operation with a stride greater than one spoils symmetry under translations, even though a global pooling layer constitutes the transition from the convolutional part of the network to its dense part, e.g. in [27].…”
Section: Introductionmentioning
confidence: 99%